IMPLIKATUR PERCAKAPAN DALAM ANIME BERGENRE KOMEDI BERJUDUL BACK STREET GIRL’S GOKUDOLLS - Zahratul Alya Salsabila; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study focuses on analyzing flouting of conversational principle conversational maxim in anime Back Street Girl’s Gokudolls. This study is aimed to describe types of Grice’s conversational maxims frequently floated in anime Back Street Girl’s Gokudolls to describe the implicature of the floats of the maxims. The writer employs descriptive qualitative approarch to reach and conclude the research findings in this study. In analyze the writer refers to Grice’s cooperative principle theory, and means-ends analysis by Geoffrey Leech. The data was obtained by listening to the conversations spoken by the characters in the anime Back Street Girl's Gokudolls. Then the speech that flouting the maxims and cause implicatures are recorded and marked. The results of this study indicate that the characters in the anime Back Street Girl's Gokudolls flouting the four maxims of cooperation, maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner. Of the four maxims, the most flouting are in the maxim manner and the least is the flouting of the maxim of quantity.Key Word: Implicature, Cooperative Principle, Back Street Girl’s Gokudolls, Anime